ANALISIS PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON ASSETS (ROA) TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rotua Panjaitan (Departemen Ekonomi Pembangunan USU, 2013)
This study entitled influence of Credit Attempt Of Prosperous Family against the income of families in Toba Samosir regency. The purpose of this study was to determine the effect of the Credit Attempt OfProsperous Family, the number of the family, and the number of the Attempt Enhancement Of Prosperous Family to increase family income in Toba Samosir regency. The problems in this study is whether the independent variables Credit Attempt Of Prosperous Family, the number of the family, and the number of the Attempt Enhancement Of Prosperous Family simultaneously or partially affect the level of family income. The data used in this study is primary data obtained from Toba Samosir regency. The hypothesis is Credit Attempt Of Prosperous Family have positive effect on family income levels. Based on the regression results indicated that the variable Credit Attempt Of ProsperousFamily (X 1), the number of the family (X2), and Attempt Enhancement Prosperous Family (X3) have a positive and significant effect on the income of the family in Toba Samosir regency.Keywords : Credit Attempt Of Prosperous Family, the number of the family,the number of the Attempt Enhancement Of Prosperous Family, Family Income